The Impact of Emotions and Hedonic Balance on Teachers’ Self-Efficacy: Testing the Bouncing Back Effect of Positive Emotions - Buonomo, Ilaria; Fiorilli, Caterina; Benevene, Paula (Frontiers in Psychology, 2019)
Emotions towards students (e.g., Chan, 2004) and professional role (e.g., O'Connor, 2008) impact teachers’ self-efficacy beliefs. The effect of positive emotions can be explained by the broaden and build theory, stating that the higher the positive emotions individuals attribute to themselves, the higher the chance to build positive aspects of the self (Fredrickson, 2001). At the same time, negative emotions at school inversely influence TSE, reducing teachers’ confidence (Chan, 2004). Furthermore, Fredrickson (et al., 2000) studies inform about the bouncing back effect of positive emotions on the detrimental effects of negative emotions on self-efficacy. Starting from these considerations, this study 1) evaluated the bouncing back effect of positive emotions on negative ones, when predicting self-efficacy; 2) verified whether emotions towards professional role moderated the bouncing back effect. Self-Efficacy and Emotions in teaching (MESI, Moè et al., 2010) were measured. Two hundred and seventy-two Italian secondary school teachers (F=73%) were involved. Positive emotions towards students might act as buffering factors against the detrimental effect of negative emotions on self-efficacy (F(2, 270)=26.17, P <.001, R2=.199). Finally, emotions towards students and emotions towards professional role do not interact when predicting self-efficacy. The relationships with students seems to have an highly protective effect on teachers’ mental health. At the same time, the perception of one’s own role as detached from the teaching community may have a role in justifying the non-significant effect of emotions towards professional role in the model and shed new light of intervention objectives.